EMPOWERING THE PUBLIC THROUGH HEALTH LITERACY: LITERATURE STUDIES - Nunu Andriani; Sidderatul Akbar, Nooraisyah (Adiba Aisha Amira, 2023)
This research aims to understand the effectiveness of health literacy programmes in empowering the public. Emphasizing the importance of health literacy and its implications for health outcomes, the study also explores potential obstacles to the implementation of this kind of program and what strategies can be used to expand health literature. The research method used is literature review, which involves searching, evaluating, and synthesizing existing research related to health literature. This research found that health literacy plays an important role in improving health outcomes and empowering communities, by enabling individuals to make more intelligent health decisions. However, the implementation of health literacy programmes has obstacles to both resource constraints, access to information, technological problems, cultural and linguistic barriers, and society's resistance to change. Nevertheless, the survey also found various effective strategies to overcome such barriers, such as sustainable education, relatable media use, and peer-to-peer programmes, as well as the important role of governments and related institutions in providing policy support and resources.